An Experimental Study on the Formation of Natural Gas Hydrate With Thermodynamic Inhibitors - Wei, Na; Xie, Cuiying; Sun, Wantong; Li, Haitao; Jiang, Lin; Zhang, Shenghui (Frontiers in Energy Research, 2021)
Gas hydrates formed in the conditions of high pressure and low temperature in deep sea and in the process of oil and gas transportation, natural gas hydrate (NGH), will seriously affect the safety of drilling and completion operations and marine equipment and threaten the safety of drilling platform. How to prevent the hydrate formation in the process of oil and gas production and transportation has become an urgent problem for the oil and gas industry. For this reason, in view of the formation of NGH in the process of drilling and producing marine NGH, the phase equilibrium calculation research of NGH formation was carried out, the mathematical model of gas hydrate formation phase equilibrium condition was established, and the experimental research on NGH formation was carried out through adding different thermodynamic inhibitors. The experimental phenomena show that, first, the stirring speed has little effect on the inhibition of hydrate formation. Second, when the pressure is 10 MPa and the volume concentration of inhibitor is 1, 3, 5, and 7%, the supercooling degree of hydrate formation is 1.81, 8.89, 11.09, and 9.39°C, respectively. Third, when the volume concentration of inhibitor is 1, 3, 5, and 7%, the induction time of hydrate formation is 10328, 14231, 19576, and 24900 s, respectively. As the polymer molecules in the inhibitor reduce the activity of water in the system and fill the cavity structure of the hydrate, they reduce the generation conditions of NGH and break the original phase equilibrium conditions when NGH is generated, thus forming NGH at a lower temperature or higher pressure.